Pengaruh Dana Tabarru dan Hasil Underwriting terhadap Return On Asset - Riady, Achmad; Hidayat, Rahmat Wahyu (Politeknik Baubau, 2024)
Tabarru funds are contributions issued by sharia insurance policies which are intended to be given and used to help sharia insurance participants if a disaster strikes. Meanwhile, the underwriting result is a score obtained from the difference between insurance income and underwriting expenses from the main insurance activities, the activities of which will generate and increase the company's profits. Return on assets is a ratio to see the level of profitability of an institution, where in this case ROA is used to see how great the company's ability to gain profits through the use of its assets or assets, in this case a sharia life insurance company. This research aims to determine the effect of tabarru funds, underwriting results on ROA on sharia life insurance registered with the OJK for the 2018-2022 period. This type of research is quantitative research. The sample used is time series data of monthly financial reports of sharia life insurance registered with the OJK for the 2018-2022 period with a total of 60 samples. The data analysis technique used in this research is descriptive statistics using multiple linear regression analysis with the help of SPSS. The research results show that partially tabarru funds have a negative and significant effect on ROA in sharia life insurance. Partially, underwriting results have a positive and significant effect on ROA in sharia life insurance. Simultaneously tabarru funds and underwriting results have a positive and significant effect on ROA in sharia life insurance. The implication of this research is that if sharia life insurance focuses on tabarru fund management and further improves underwriting results, it will produce stable financial reports so that it has the opportunity to increase profits in terms of profit.